(untitled) (Bangladesh Journal of Medical Science, 2016)
Introduction: A genetic polymorphism has been identified inside the CD14 Promoter sequence. It consists of a C to T transition at base pair -159 from the major transcription site. Subjects carrying the T allele have been shown to have significantly higher soluble CD14 levels than do carriers of the C allele. Consequently, genetic variations in CD14 particularly polymorphism located on the promoter region are thought to have functional effects and increased susceptibility to sepsis. Methods: Our study was a case control study in which a total of 85 samples were included out of which 50 were sepsis free controls and 35 cases of sepsis. Both the cases and controls were selected from Surgical Intensive Care Unit of Sher-i-Kashmir Institute of Medical Sciences (SKIMS), Srinagar. Age more than 80 years, cardiac failure, liver insufficiency and cancer patients were excluded from the study. 5ml of blood from peripheral vein was obtained from each subject in EDTA containing vials and DNA extraction was done by salting out method. Results: The TT genotype frequency was significantly higher in sepsis than in control (P=0.025) and appeared to be genetic risk factor for increased susceptibility to sepsis. The frequency of mutant T allele observed in cases was 36(51.4%) and 35(35%) in controls. This observation showed a highly statistically significant of rare allele T between cases and controls (P=0.033). Patients with increased Total Leucocytes Count (TLC) were more significantly associated with combined (CT+TT) against CC against those patients with normal TLC (P<0.01). The cases had a higher frequency of the rare allele (CT+TT = 80%) than the controls (64%) and this difference showed statistically insignificant association with CT + TT combination against CC (P=0.11). Conclusion: The present study suggested that CD14-159C>T may be a risk factor for the development of sepsis in Kashmiri Population. Bangladesh Journal of Medical Science Vol.15(4) 2016 p.538-545